To solve the equation x + 2/1/3 = 5/2/3, we need to isolate x by applying inverse operations.
First, let's simplify the right side of the equation. The fractions 2/1/3 and 5/2/3 can be rewritten as mixed numbers.
2/1/3 = 2 + 1/3
5/2/3 = 5 + 2/3
Now we have x + 2 + 1/3 = 5 + 2/3.
Next, let's subtract 2 from both sides of the equation to eliminate the 2 on the left side:
x + 1/3 = 5 - 2 + 2/3
x + 1/3 = 2 + 2/3
To eliminate the 1/3 on the left side, we need to subtract 1/3 from both sides:
x + 1/3 - 1/3 = 2 + 2/3 - 1/3
x = 2 + 2/3 - 1/3
Now we can simplify the right side of the equation by finding a common denominator for 2/3 and 1/3, which is 3.
x = 2 + (2 - 1) / 3
x = 2 + 1/3
Finally, we can write x = 2 + 1/3 as a mixed number:
x = 2 + 1/3 = 6/3 + 1/3 = 7/3
Therefore, x = 7/3.
Solve the equation x+2/1/3=5/2/3 using inverse operations.(1 point) x=
3 answers
rong
Apologies for the mistake in my previous response. Let's solve the equation again:
To solve the equation x + 2/1/3 = 5/2/3, we need to simplify the fractions and then isolate x.
First, let's simplify the fractions.
2/1/3 can be written as (2 * 3 + 1) / 3 = 7 / 3
5/2/3 can be written as (5 * 3 + 2) / 3 = 17 / 3
Now, the equation becomes x + 7/3 = 17/3.
Next, let's isolate x by subtracting 7/3 from both sides of the equation:
x + 7/3 - 7/3 = 17/3 - 7/3
x = 10/3
Therefore, x = 10/3 is the solution to the equation.
To solve the equation x + 2/1/3 = 5/2/3, we need to simplify the fractions and then isolate x.
First, let's simplify the fractions.
2/1/3 can be written as (2 * 3 + 1) / 3 = 7 / 3
5/2/3 can be written as (5 * 3 + 2) / 3 = 17 / 3
Now, the equation becomes x + 7/3 = 17/3.
Next, let's isolate x by subtracting 7/3 from both sides of the equation:
x + 7/3 - 7/3 = 17/3 - 7/3
x = 10/3
Therefore, x = 10/3 is the solution to the equation.